PENGARUH TERAPI EMOTIONAL FREEDOM TECHNIQUE (EFT) TERHADAP PENURUNAN SKALA NYERI DISMENOREA PADA REMAJA - lenni sastra (Jurnal Ipteks Terapan, 2014)
ABSTRACTDysmenorrheal is pain during menstruation. Pain can be minimized using pharmacological and non pharmacological therapies.  One of them is emotional freedom technique (EFT). The purpose of this study was to determine the effect of EFT therapy to decrease pain scale dysmenorrheal in adolescents at high school N 12 of Padang. It was a quasi-experimental, with two group design with pretest-posttest control group. The collection of data was carried at 12 public senior high school Padang. The number of samples  were 40 people, 20 of experimental group and 20 of control group were taken using purposive sampling technique. Combination of numeric rating scale (NRS) and Hayward were used to collect data. Data were analyzed using wilcoxon test and mann-whitney statistical test. The results showed that pain pretest adolescent experimental group was 95% moderate pain and pain scale post-test was 100% mild pain, while the pain scale test of the first on adolescent group control is 70% moderate pain and pain scale on the test II 70% pain moderate. Wilcoxon and mann-whitney test obtained p value = 0.00 means there was differences decrease pain scale between the experimental group and control group. Based on the results it can be concluded there was the influence of EFT therapy to decrease pain scale dysmenorrheal for adolescents at 12 public senior high school Padang. Suggestions for teenagers to be able to use EFT therapy to relieve pain during dysmenorrheal and suggestions for schools to be able to provide EFT therapy education.  ABSTRAKDismenorea adalah nyeri sewaktu haid yang sering dialami oleh remaja putri. Nyeri dapat diminimalkan dengan terapi farmakologis dan non farmakologis. Salah satunya adalah terapi emotional freedom technique (EFT). Tujuan penelitian untuk mengetahui pengaruh terapi EFT terhadap penurunan skala  nyeri dismenorea pada remaja di SMA N 12 Kota Padang. Jenis penelitian adalah quasi-eksperiment, dengan two group pretest-posttest with control group. Pengumpulan data dilaksanakan di SMA N 12 Kota Padang. Jumlah sampel adalah 40 orang, 20 kelompok eksperimen dan 20 kelompok kontrol yang diambil dengan teknik purposive sampling. Instrumen yang digunakan gabungan numeric rating scale (NRS) dan Hayward. Data dianalisis dengan uji statistic wilcoxon dan mann whitney. Hasil penelitian menunjukkan bahwa nyeri pretest pada remaja kelompok eksperimen adalah 95% nyeri sedang  dan skala nyeri postes adalah 100% nyeri ringan, sedangkan skala nyeri uji I pada remaja kelompok kontrol adalah 70% nyeri sedang dan skala nyeri  pada uji II 70% nyeri sedang. Hasil uji statistik wilcoxon dan mann-whitney  didapatkan hasil p value < 0.00 artinya terapi emotional freedom technique (EFT) berpengaruh terhadap penurunan skala nyeri dismenore pada remaja. Berdasarkan hasil dapat disimpulkan ada pengaruh terapi EFT terhadap penurunan skala nyeri dismenorea pada pemaja. Saran bagi sekolah untuk dapat memberikan penyuluhan terapi EFT.